2013
DOI: 10.2319/071113-510.1
|View full text |Cite
|
Sign up to set email alerts
|

Parents' preferences regarding appearance and attire of orthodontists

Abstract: Parents of orthodontic patients demonstrated clear preferences for choosing a provider related to factors that are not within the control of the practitioner (sex and age) as well as factors that can be changed by the practitioner (attire, hairstyle, and wearing a nametag).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
3
8
0
4
Order By: Relevance
“…However, our results showed that both parents (13%) and children (7%) were less likely in favor of casual attire which agrees with the findings of Kelly GR et al 22 Despite recent changes in western culture toward casual dress it appears that both older and younger generation continue to expect a dentist to be formally dressed. A highly significant difference in gender preference was found with males favoring male students and females female students (χ 2 = 47.16, p < 0.001) confirming the findings of Mistry et al and AlSarheed.…”
Section: Discussionsupporting
confidence: 90%
“…However, our results showed that both parents (13%) and children (7%) were less likely in favor of casual attire which agrees with the findings of Kelly GR et al 22 Despite recent changes in western culture toward casual dress it appears that both older and younger generation continue to expect a dentist to be formally dressed. A highly significant difference in gender preference was found with males favoring male students and females female students (χ 2 = 47.16, p < 0.001) confirming the findings of Mistry et al and AlSarheed.…”
Section: Discussionsupporting
confidence: 90%
“…The patient-doctor interaction should be emphasized during professional graduate and postgraduate education. In a study conducted among parents of orthodontic patients, the parents showed a positive preference for orthodontists to wear formal attire or scrubs, to have controlled hair, and to have a nametag, and preferred younger women and older men (14). In our study, we did not evaluate patients' preference for OMFS attire, but the physically strong appearance of the surgeon did not influence the patients' choice.…”
Section: Discussionmentioning
confidence: 71%
“…The practitioner's age may influence the patient's preference, but there is a lack of evidence. Patients may prefer middle-aged or older practitioners because they feel that medical experience increases with age (2,5,14). Another question that needs to be answered is whether patients prefer practitioners 140 Gürler et al who are a similar age to themselves.…”
Section: Discussionmentioning
confidence: 99%
“…The 400 adults interviewed, with a mean age of 52.4, preferred that physicians wore white coats because they reported that it would be the form Professional Of Dress Up, offering greater confidence and credibility to the patient (Tibdewal et al, 2010;Chung et al, 2012) [5,17] . More patients than dentists, and especially The adults, Believe that the dentist should wear white garments as differential for easy identification (Kelly et al, 2014) [18] . A literature review (Kazory, Indme 2008) [19] , there was a decline in the popularity of the white coat among physicians.…”
Section: Discussionmentioning
confidence: 99%